2001
DOI: 10.1302/0301-620x.83b7.12195
|View full text |Cite
|
Sign up to set email alerts
|

Measuring physical activity in patients after surgery for a malignant tumour in the leg

Abstract: A continuous ambulatory activity monitor allows objective measurement of the amount and intensity of physical activity. We examined the reliability and validity of this device in the assessment of seven aspects of function over a period of 24 hours in 20 patients who had undergone limb salvage or amputation for a tumour in the leg. The test-retest reliability was determined by undertaking identical assessments on two separate days. The measurements were compared with other indicators of functional status and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 15 publications
2
31
1
Order By: Relevance
“…Patients scheduled for knee replacement showed a higher level of locomotion and movement intensity compared to COPD patients [21] and amputees [26] and similar duration of locomotion compared to healthy adults [21,22]. However, they displayed lower movement intensities [21].…”
Section: Discussionmentioning
confidence: 92%
“…Patients scheduled for knee replacement showed a higher level of locomotion and movement intensity compared to COPD patients [21] and amputees [26] and similar duration of locomotion compared to healthy adults [21,22]. However, they displayed lower movement intensities [21].…”
Section: Discussionmentioning
confidence: 92%
“…A major limitation of the study was the inaccuracy of the pedometer, which was found to undercount steps by approximately 40%. Van Dam et al 12 used a 3-dimensional accelerometer to document total physical activity and walking over a 24-hour period in 20 patients who had undergone limb salvage surgery and found that their patients spent approximately 5.6% of the 24 hours walking versus standing or sitting.…”
Section: Discussionmentioning
confidence: 99%
“…Since there are no differences in survival rates between limb‐salvage (LS) and ablative surgery (AS), long‐term functional outcome studies have become increasingly important to make a patient specific surgical decision . However, comparability of these studies is complicated because of the use of different research design, different kind of functional tests and questionnaires, various anatomic sites, a wide range of ages and follow‐up …”
Section: Introductionmentioning
confidence: 99%